Biosurfactants: Current application trends - M.A. Rudakova; P.Yu. Galitskaya; S.Yu. Selivanovskaya (Учёные записки Казанского университета: Серия Естественные науки)
This paper discusses the latest trends in studying and using biosurfactants, surfactant biomolecules produced by microorganisms. Biosurfactants were considered as an alternative to synthetic surfactants. The basic principles of producing, screening and characterizing biosurfactants were reviewed. Their physicochemical properties were singled out. The modern understanding of a relationship between the properties of biosurfactants and their practical use was analyzed. Particular attention was paid to the research works focused on the potential use of biosurfactants, as well as the current and major challenges of their production and application in the real sector of economy. The already existing world biosurfactant market was described. An outlook on its possible future development was provided.